Programa educativo aprendizaje cooperativo en el logro de la competencia construye su identidad en el área de desarrollo personal ciudadanía y cívica en los estudiantes del cuarto grado de educación secundaria del colegio Teniente Manuel Clavero Muga 2022 - Cachique Nashnate, Frida Geraldine (2023)
The objective of this research was: To evaluate the effect of the cooperative learning educational program on the achievement of competence builds their identity in the area of personal development, citizenship and civics in fourth grade students, secondary level at the educational institution “Teniente Manuel Clavero Muga” district of Punchana 2022. The study allowed us to reach the conclusion that the cooperative learning educational program is effective in achieving the competence it builds its identity and also in its capabilities because the achievement obtained thanks to the application of the educational program was better than that obtained with the traditional method. It encourages the achievement of capacity: it self-regulates its emotions, values itself, and reflects and argues ethically.